(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article intends to compare the impact of bilingualism on the reading skills of Azeri and Persian language students in Tabriz. This is a quantitative study. Data is gathered by pre-post tests that are about problems arising from bilingualism. The results show that students of this Azeri-spoken city did better in their reading skills which are caused by bilingualism during their education.